The evolution of parasitism : a phylogenetic perspective - Littlewood, D. T. J. (D. Timothy J.), 1961- (Amsterdam ; Boston : Elsevier Academic, 2003)
Parasitology continues to benefit from taking an evolutionary approach to its study. Tree construction, character-mapping, tree-based evolutionary interpretation, and other developments in molecular and morphological phylogenetics have had a profound influence and have shed new light on the very nature of host-parasite relations and their coevolution. Life cycle complexity, parasite ecology and the origins and evolution of parasitism itself are all underpinned by an understanding of phylogeny.
Cryptic Organelles in Parasitic Protists and Fungi -- Phylogenetic Insights into the Evolution of Parasitism in Hymenoptera -- Nematoda: Genes, Genomes and the Evolution of Parasitism -- Life Cycle Evolution in the Digenea: a New Perspective from Phylogeny -- Progress in Malaria Research: the Case for Phylogenetics --Phylogenies, the Comparative Method and Parasite Evolutionary Ecology -- Recent Results in Cophylogeny Mapping -- Inference of Viral Evolutionary Rates from Molecular Sequences -- Detecting Adaptive Molecular Evolution: Additional Tools for the Parasitologist.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Parasitology; SCIENCE -- Life Sciences -- Zoology -- General; Parasitology; Parasitologie; Parasieten; Evolutie; Electronic books